Effect of CaCl2 Concentration (Calcium Clorida) and Drying Temperature on the Characteristic of Tabah Bamboo Shoots Flour (Gigantochloa nigrociliata Buse-Kurz) - Ambarita, Juliana; Kencana, Pande Ketut Diah; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Tabahbamboo shoots are young shoots of bamboo that grow from the base of a bamboo clump which has a lot of nutrition so that it requires continuous treatment to maintain the quality. One effort that can be done is to use the concentration of CaCl2and temperature. The use of concentration CaCl2has many benefits, of which it is easy to apply and can prevent food collation from becoming soft as a result of the processing and heating effect. The research was carried out to determine the CaCl2concentrations and the correct drying temperature of tabah bamboo shoots flour. The study used a completely randomized design (CRD) which consisted of two factors, the first factor used in the research design is a CaCl2concentration of worms and the second factor used is drying temperature. The first factor consists of four levels, CaCl2concentrations 0%, CaCl2concentrations 2%, CaCl2concentrations 4%, CaCl2concentrations 6%. The second factor is three degrees, drying temperature 60°C, 70°C, and 80°C. The parameter observed in the study consist of yield, water level, ash content, protein levels, rough fibers, colors, and organoleptic test consisting of the color, aroma, texture, and overall acceptance of the hedonic test. The best treatment combination is a CaCl26% and drying temperature 80°C, which result in water 10,70%, ashes level 24,23%, protein level 24,38%, roughly fiber 18,13%, aroma 2,90, color L 86,85 and b 8,15.